2009
DOI: 10.2174/157016409789973734
|View full text |Cite
|
Sign up to set email alerts
|

Computational Analysis of Amino Acid Mutation: A Proteome Wide Perspective

Abstract: Amino acid mutations may have diverse effects on protein structure and function. Thus reliable information about the protein sequence variations is essential to gain insights into disease genotype-phenotype correlations. With the recent availability of the complete genome sequence and the accumulation of variation data, determining the effects of amino acid substitution will be the next challenge in mutation research. The molecular consequences of amino acid mutations can readily be predicted by numerous bioin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 62 publications
(76 reference statements)
0
26
0
Order By: Relevance
“…Initially, the SNP data were extracted from the NCBI database and nsSNPs were sorted for further computational analysis by different bioinformatics tools. Various tools like SIFT Blink, PolyPhen‐2, I‐Mutant2.0, and PANTHER are helpful in predicting the functional phenotypes of nsSNPs based on protein structure, protein sequence cross species conservation, and physicochemical properties . Previous studies have reported that using multiple tools and algorithms for prioritizing functional mutations enhances the accuracy of prediction .…”
Section: Discussionmentioning
confidence: 99%
“…Initially, the SNP data were extracted from the NCBI database and nsSNPs were sorted for further computational analysis by different bioinformatics tools. Various tools like SIFT Blink, PolyPhen‐2, I‐Mutant2.0, and PANTHER are helpful in predicting the functional phenotypes of nsSNPs based on protein structure, protein sequence cross species conservation, and physicochemical properties . Previous studies have reported that using multiple tools and algorithms for prioritizing functional mutations enhances the accuracy of prediction .…”
Section: Discussionmentioning
confidence: 99%
“…Stability is the fundamental property enhancing biomolecular function, activity, and regulation. Structural mutations affected buried residues in the protein core, causing changes in amino acid size, amino acid charge and hydrogen bond numbers [ 47 ]. Hydrogen bonds are the most important factor that creates a stable contact between a protein and its binding partner.…”
Section: Discussionmentioning
confidence: 99%
“…In all these cases we can find models that use the structural parameters of molecular systems like drugs, protein structure, RNA secondary structure, protein-protein interaction networks (PINs), genes network as input to predict the properties of such system (output). That is why, the editor González-Díaz has extended the discussion to different collective of authors editing special issues on CADD techniques (including QSAR and others), which have been published on journals such as the Current Topics in Medicinal Chemistry [19][20][21][22][23][24][25][26][27][28], Current Proteomics [29][30][31][32][33][34][35][36], Current Drug Metabolism [37][38][39][40][41][42][43][44][45], Current Pharmaceutical Design [46][47][48][49][50][51][52][53][54][55], and Current Bioinformatics [56][57][58][59][60][61][62][63]…”
Section: Cadd Methodologies For the Discovery Of Drugs And Targetsmentioning
confidence: 99%